Recapitulating the clinical scenario of BRCA‐associated pancreatic cancer in pre‐clinical models. Issue 1 (23rd February 2018) - Golan, Talia; Stossel, Chani; Atias, Dikla; Buzhor, Ella; Halperin, Sharon; Cohen, Keren; Raitses‐Gurevich, Maria; Glick, Yulia; Raskin, Stephen; Yehuda, Daniel; Feldman, Anna; Schvimer, Michael; et al.
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies. BRCA ‐associated PDAC comprises a clinically relevant subtype. A portion of these patients are highly susceptible to DNA damaging therapeutics, however, responses are heterogeneous and clinical resistance evolves. We have developed unique patient‐derived xenograft (PDX) models from metastatic lesions of germline BRCA ‐mutated patients obtained at distinct time points; before treatment and at progression. Thus, closely mimicking clinical scenarios, to further investigate treatment naïve and resistant patients. DNA was isolated from six BRCA ‐mutated PDXs and classified by whole‐genome sequencing to stable‐genome or homologous recombination deficient (HRD)‐genome. The sensitivity to DNA‐damaging agents was evaluated in vivo in three BRCA ‐associated PDAC PDXs models: (1) HRD‐genome naïve to treatments; (2) stable‐genome naïve to treatment; (3) HRD‐genome resistant to treatment. Correlation between disease course at tissue acquisition and response to PARP inhibitor (PARPi)/platinum was demonstrated in PDXs in vivo . Only the HRD‐genome PDX, naïve to treatment, was sensitive to PARP inhibitor/cisplatin treatments. Our results demonstrate heterogeneous responses to DNA damaging agents/PARPi in BRCA ‐associated PDX thus reflecting the wide clinical spectrum. An HRD‐genome PDX generated from a naïve to treatment biopsy was sensitive to platinum/PARPi whereas no benefit was observed in treating a HRD‐genome PDXs generated from a patient that had acquired resistance nor stable‐genome PDXs. Abstract : What's new? Improving the prognosis of pancreatic ductal adenocarcinoma (PDAC) is challenged in part by limited knowledge of relationships between PDAC subtypes and therapeutic responses. Here, using patient‐derived xenograft (PDX) models from BRCA1/2 PDAC patients before and after treatment, the authors describe a correlation between clinical subtypes, therapeutic time points, and responses to platinum and PARP inhibition (PARPi) therapy. In particular, a treatment‐naive PDX with homologous recombination deficiency (HRD) was sensitive to platinum/PARPi therapy, whereas no benefit was observed in an HRD‐genome PDX with acquired resistance. The findings warrant investigation of the effects of alternative combination therapies selected based on PDAC subtype.